JUSTICE FOR CHILDREN IN ARGENTINA: A BACKLASH TO CONSERVATIVE DISCOURSES - RODRIGUEZ, YAMILA VANESA (Society Register, 2019)
The author uses Critical Discourse Analysis to compare two legal documents of critical relevance for the rights of children in conflict with the law in Argentina: the current law no. 22,278, called Régimen Penal de la Minoridad, and the project named Sistema de Responsabilidad Penal Juvenil which was under consideration by the National Congress during 2019. This project was proposed by the government so as to stablish a new juvenile justice system in Argentina, following a widely spread tendency in the Latin American region. The purpose of the article is to show that, even though the language of human rights is used in official discourse and in the legal text submitted to Parliament, many of its features represent a clear backlash to a more conservative regime.